A Review of Fecal Microbiota Transplantation in Children—Exploring Its Role in the Treatment of Inflammatory Bowel Diseases - Yanna Ko; Sara Alaedin; Dewni Fernando; Jerry Zhou; Vincent Ho (Medicina, 2024)
Background and Objectives: There is an increasing use of fecal matter transplantation (FMT) worldwide as research into the impact of the gut microbiome in various disease states is growing. FMT is the transfer of stool from a healthy human donor to a patient for the purpose of restoring intestinal dysbiosis. This review will assess the efficacy and safety of FMT in the treatment of pediatric inflammatory bowel diseases (IBDs) and explore the future directions of the use of FMT in children. Materials and Methods: A systematic review was performed where a literature search of publications published prior to 15 September 2023 was performed. Efficacy outcomes and safety data as well as microbiome analysis were reviewed from the studies where applicable. Results: Nine studies on UC and two studies on CD satisfied eligibility criteria and individually analysed. Most of the studies provided microbiome analyses. Conclusions: FMT is a safe treatment for paediatric IBD, and is shown to be effective in inducing clinical response by some studies. However the lack of randomized controlled trials limited the results of our study.